2016
DOI: 10.3928/01477447-20160419-06
|View full text |Cite
|
Sign up to set email alerts
|

Total Joint Arthroplasty in a Stand-alone Ambulatory Surgical Center: Short-term Outcomes

Abstract: A mbulatory surgical centers (ASCs) offer surgeons an effective setting to perform procedures that do not require prolonged postoperative monitoring or an inpatient hospital stay. Advances in minimally invasive surgical techniques, short-acting general anesthetics, long-acting local anesthetics, and blood loss management have improved the safety and recovery for many orthopedic procedures. These changes to perioperative care have reduced the need for postoperative hospitalization in many surgical specialties. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 33 publications
2
56
1
Order By: Relevance
“…The benefits of outpatient arthroplasty are reported to include higher patient satisfaction and reduced costs [15,29]. Multiple studies comparing the outcomes of inpatient with outpatient arthroplasty have been reported [2,5,9,10,15,16,24,25,29,30,37,40,48]. However, the difference between ''inpatient'' and ''outpatient'' is not as intuitive as one might think.…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…The benefits of outpatient arthroplasty are reported to include higher patient satisfaction and reduced costs [15,29]. Multiple studies comparing the outcomes of inpatient with outpatient arthroplasty have been reported [2,5,9,10,15,16,24,25,29,30,37,40,48]. However, the difference between ''inpatient'' and ''outpatient'' is not as intuitive as one might think.…”
Section: Introductionmentioning
confidence: 74%
“…The recent changes in healthcare insurance and the aging US population make the appropriate exploration of outpatient procedures in terms of safety and cost-effectiveness more important than ever. The large number of recent orthopaedic studies comparing inpatient and outpatient procedures underscores this importance [2,5,9,10,15,16,24,25,29,30,37,40,48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Not all patients are candidates for outpatient joint arthroplasty (OJA); however, careful selection of appropriate patients can allow for successful outpatient surgery and recovery at home. Assessing surgical risk is necessary to determine which patients are best suited for this type of postoperative care . Although the tools for selecting suitable candidates are still being refined, several tools are currently used .…”
Section: Outpatient Selection Criteriamentioning
confidence: 99%
“…Although the tools for selecting suitable candidates are still being refined, several tools are currently used . The American Society of Anesthesiologists’ classification, the Charlson comorbidity index (CCI), and the Outpatient Arthroplasty Risk Assessment all have merit . The American Society of Anesthesiologists’ rating scale measures fitness for surgery .…”
Section: Outpatient Selection Criteriamentioning
confidence: 99%